Productivity Labour Adjustment Costs. How do new hires and leavers (incl. retirees) compare? - Vincent Vandenberghe (Global Labor Organization (GLO), 2025)
Labour turnover is a crucial element of contemporary economic life. It can improve productivity if more productive workers replace less productive ones. However, in the short run, it generates sizeable labour adjustment costs (LACs), including productivity losses. This paper sheds new light on the turnover-productivity relationship focusing on productivity LACs. We use firm-level 2014-2022 Belgian data with information on stayers, new hires and leavers: those who are fired, those leaving voluntarily, and those who are about to retire. We use the Hellerstein-Neumark (HN) framework to quantify the productivity of these different labour types, using stayers as a benchmark. We posit that evidence of significant productivity handicaps is a good indicator of productivity LACs. Results suggest no productivity LACs for new hires. By contrast, for leavers, they point to significant ones. What is more, findings for prospective (early) retirees indicate a very sizeable drop in productivity during their last year of employment.
Keywords: J24; J63; J26; 330; Labour Turnover; Labour Adjustment Costs; Labour Productivity Differences; Prospective Retirees; Short Horizon